Lateral entry pins and Slongo’s external fixation: which method is more ideal for older children with supracondylar humeral fractures? - He, Man (J Orthop Surg Res, 2021)
OBJECTIVE: The standard surgical treatment for supracondylar humeral fractures in children is closed reduction and percutaneous pinning. Given the need for greater fixation strength and higher risk of joint stiffness for children older than 8 years, external fixation is often performed for treating supracondylar humeral fractures in older children. The aim of this study was to compare the efficacy of lateral entry pins and Slongo’s external fixation for treating supracondylar humeral fractures in older children. METHODS: Children older than 8 years who underwent surgery for supracondylar humeral fractures at our hospital for surgery from January 2016 to December 2020 are to be retrospectively assessed. One group (n = 36) underwent internal fixation and percutaneous pinning with three lateral Kirschner wires, and the other group (n = 32) underwent Slongo’s external fixator surgery. The demographic data, operation duration, number of fluoroscopies, and fracture healing time were compared between both groups. The elbow joint function was evaluated 6 months after the surgery on the basis of fracture healing time, lifting angle, elbow joint range of motion (ROM), and Flynn score. The incidence of postoperative complications was also recorded. RESULTS: There was no significant difference between the two patient groups in terms of the demographic parameters. Compared to external fixation surgery, Kirschner wire surgery required shorter duration and fewer fluoroscopies (P < 0.05). Nevertheless, the fracture healing time was significantly less (P < 0.05), and the elbow ROM and Flynn scores were higher in the external fixator group compared to the Kirschner wire fixation group (P < 0.05). There was one case of secondary fracture displacement in the Kirschner wire group and one of pin tract infection in the external fixator group. No other iatrogenic injuries or complications were observed. CONCLUSION: Maybe Slongo’s external fixator is a suitable alternative treatment option for supracondylar humeral fractures in children older than 8 years since it can achieve better fixation strength and early restoration of elbow joint movement with a lower risk of joint stiffness. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13018-021-02541-z.